2017
DOI: 10.1016/j.bbi.2017.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Mothers’ childhood hardship forecasts adverse pregnancy outcomes: Role of inflammatory, lifestyle, and psychosocial pathways

Abstract: Research suggests the health consequences of economic hardship can be transmitted across generations. Some of these disparities are thought to be passed to offspring during gestation. But this hypothesis has not been tested in contemporary American samples, and the mechanisms of transmission have not been characterized. Accordingly, this study had two goals: first, to determine if women exposed to economic hardship during childhood showed higher rates of adverse birth outcomes; and second, to evaluate the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 53 publications
4
38
1
Order By: Relevance
“…Consistent with the larger literature (Miller et al, 2017; Mitchell et al, 2018; Walsh et al, 2016), the current study provides further evidence that adversities experienced during childhood and adulthood are associated with elevated inflammatory markers during pregnancy. Specifically, bivariate correlations revealed that a history of childhood abuse was positively associated with both CRP and IL-6 in a sample of pregnant women, while current SES was negatively associated with both CRP and IL-6.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with the larger literature (Miller et al, 2017; Mitchell et al, 2018; Walsh et al, 2016), the current study provides further evidence that adversities experienced during childhood and adulthood are associated with elevated inflammatory markers during pregnancy. Specifically, bivariate correlations revealed that a history of childhood abuse was positively associated with both CRP and IL-6 in a sample of pregnant women, while current SES was negatively associated with both CRP and IL-6.…”
Section: Discussionsupporting
confidence: 90%
“…One risk factor that has been linked to excessive inflammation during pregnancy is exposure to chronic adversity. Women who have experienced significant adversities during childhood (e.g., abuse) and adulthood (e.g., poverty or low socioeconomic conditions) are at risk for excessive inflammation, which has implications for pregnancy (Miller et al, 2017; Mitchell et al, 2018; Walsh et al, 2016). A history of childhood exposure to abuse and low socioeconomic status (SES) have been independently associated with a chronic inflammatory state characterized by elevations in inflammatory markers across the lifespan (Azad et al, 2012; Baumeister et al, 2016; Danese et al, 2007; Pollitt et al, 2008), in addition to adverse pregnancy outcomes characterized by excessive inflammation (Bushnik et al, 2017; Gavin et al, 2012; Silva et al, 2008; Smith et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In all, there were 744 women at visit A and 639 at visit B; ultimately, 686 post-delivery medical records, such as pregnancy outcomes, were available. Additional details about the original data collection can be found in prior publications [14]. Ethics approval for the original data collection was provided by the Institutional Review Board of Northwestern University in Evanston IL, project number STU00039484.…”
Section: Methodsmentioning
confidence: 99%
“…The contexts informing individual development also may be distal: transgenerational sex‐specific effects of parental as well as grandparental circumstances on descendants’ maturation, health, and survivorship increasingly have been documented (Pembrey et al., ). Maternal hardship in early life increases likelihood of poor outcomes of pregnancy including low birth weight (G. E. Miller et al., ), which is known to be associated with offspring age at menarche and long‐term health outcomes (Adair, ). In addition, evidence has been accumulating for age‐specific (pre vs. late puberty) effects of paternal nutrition on offspring health across one or two generations (Isganaitis, Suehiro, & Cardona, ; Rando, ).…”
Section: Theoretical and Conceptual Advancesmentioning
confidence: 99%